The Oxford Finger Nail Appearance Score - a new scoring system for fingernail deformity following paediatric finger tip trauma. Issue 1 (January 2021) - Jain, Abhilash; Stokes, Jamie; Gardiner, Matthew D.; Cook, Jonathan A.; Jones, Amy; Cooper, Cushla; Shirkey, Beverly; Sierakowski, Adam; Beard, David; Greig, Aina V.H.; Dupré, Sophie; Adami, Raina Zarb; et al.
Summary: Fingernail deformity is common, yet current methods used to define cosmetic appearance following trauma are mainly descriptive. In order to quantify the cosmetic appearance of the fingernail, we developed the Oxford Fingernail Appearance Score using a three stage iterative process. The score has five cosmetic components marked as binary outcomes composed of nail shape, nail adherence, eponychial appearance, nail surface appearance and presence of a split. In the first stage, two assessors independently assessed 25 photographs of fingernails taken at a minimum of four months following paediatric nail bed repair and compared them to the corresponding contralateral uninjured finger. Following refinement in the score, ten different assessors scored a further 62 photographs of fingernails taken after paediatric nail bed repair. Assessors completed each of the five components, and the overall component score was calculated by statisticians post-hoc, taking the ideal appearance of each component as 1 ("identical to opposite" for nail shape, eponychium and surface, "complete" for adherence, "absent" for split) and all the non-ideal appearances as 0. Assessors effectively scored the photographs' integer values between 0 (least optimal appearance) and 5 (most optimal appearance). Refinements in the scoring system resulted in an improvement in a weighted kappa statistic of 0.36 (95% CI:0.09, 0.68) in the initial score to 0.52 (95% CI: 0.42, 0.61). The Oxford Fingernail Appearance Score is a user-friendly and reliable scoring system which has application in a clinical trial setting.